Research on Diameter Protocol Monitoring Scheme of S6a Interface in LTE Network Tester - Chaoyang Wang; Longhan Cao; Zhizhong Zhang (Dianxin kexue)
On the basis of introducing the functions of LTE network tester, the Diameter protocol's basic concept and functions of S6a interface were described, and the Diameter protocol monitoring scheme were designed. In consideration of the characteristics of Diameter message structure, the Diameter protocol decoding scheme was designed with the idea of modularization. Previous networks monitoring technology for CDR synthetic has the problem of insufficient timeliness, so a new CDR synthetic scheme with caching index algorithm and overtime management mechanism was proposed. It ensures the effectiveness and the validity of CDR synthetic, greatly improving the efficiency of synthesis. Using the LTE networks data to test the scheme, the results are accurate and the effects are good.